Принцип законності: наукові реалії сьогодення - Оніщенко, Н.М. (Альманах права, 2012)
Принципи права — категорія, яка займає одне з провідних місць в загальній теорії держави і права. Серед основоположних принципів: справедливості, гідності, гуманізму. Втім, на наш погляд, є невиправданим майже повна відсутність серйозних монографічних досліджень, присвячених принципу законності, його сутності, природі та значенню в умовах сучасного правового розвитку. Принципы права — категория, которая занимает одно из ведущих мест в общей теории государства и права. Среди основополагающих принципов: справедливости, достоинства, гуманизма. Впрочем, на наш взгляд, является неоправданным почти полное отсутствие серьезных монографических исследований, посвященных принципу законности, его сущности, природе и значению в условиях современного правового развития. It should be noted that the category «right» in Ukrainian language has the same root with such terms as righteous, right (proper) and fair. We would also like to connect such category as «principles» with «the adherence to principles». Now more than ever before the right should be «right» («correct»), «righteous» and «principal». In this context the fundamental principles and concepts of equality, justice, humanity, democracy, and dignity are very important. However, it is important not only to declare certain principles, but also to secure them. Thus, we should draw attention to the principle of legality. One of the shocking features of our humanitarian editorial space and recently published legal works is the lack of
serious monographs and even articles associated with the category of «legality», which almost has disappeared from the scientific use and popular science publications. There is no doubt that such situation is not dictated by significant improvements in all spheres of human life, beginning from working conditions up to the relaxation and rest. The current crisis and its manifestations generate sustainable social and legal nihilism that are transformed today from the sphere of emotions, feelings, sensations and emotions (legal psychology) into the sphere of beliefs, attitudes, ideas and stereotypes (legal ideology). This stipulates a certain type of this or that behaviour of the individual, which is unfortunately not always desirable for society. Not paying special attention to the analysis of the reasons of such phenomenon (all of them are well-known for the average citizens as well as for statesmen, officials, politicians and scientists etc.) we would like only to emphasize that Ukraine today is called a country with repressive economy, and the imperfection of its social policy is determined. The abovementioned situation causes another situation, where the government can not «reach out» to a person; people in many respects ignore not only social (moral, religious canons), but also legal norms. In our point of view, in such circumstances the revival of a respect for the principle of legality and increasing the authority of law are necessary. They are now among of the top-priority urgent tasks of the national science. Therefore, without offering new «recipes of an instant recovery of society», taking into account that this process should last not for one day, week or month, and that the society can not «recover» as if by magic, and the trust in law and regime of legality can not be immediately risen at the request of both the authorities and representatives of society, we would like to give some considerations that to our deep conviction could serve the solution of this problem, even in a staged way. First of all some general comments on the social and political content of the category of «legality» should be made. It is no exaggeration that such «contents» there were a lot of them: the revolutionary legality, proletarian legality, «red» legality, socialist legality etc. It is also understandable and clear that the other economic system has changed the idea and notion of many phenomena of social reality. But does that mean that the phenomenon of legality should be smoothed over and disappear from our life? It is no exaggeration to mention that some group of scientists believes that such a «sudden disappearance» of legality is connected with the strengthening and spread of other important principle of nowadays — the rule of law principle. But we clearly uphold the point of view that the rule of law does not oppose the principle of supremacy of laws. By the way, nowadays, as it also was long time before, the legality, efficiency and effectiveness of legislation is associated by the scholars with the law itself. Leaving aside the difficulties of our life, crisis manifestations and lesions (from the economic sphere up to the moral sphere) we would like to note that the effectiveness of law and effectiveness of legislation, interpretation of the category «legality», or if it is not seemed very ambitious, «popular legality», i.e. the regime of social and political life, which is characterized by highly respect and mandatory compliance with the provisions of the laws (from the average citizen to the officials of the highest level) acquire special significance in these conditions. At least, now there are significant grounds for this.